PROVERBS IN FERNANDO PESSOA’S WORKS - Ferrari, Patricio (Proverbium - Yearbook, 2014)
In the spring of 1914 Fernando Pessoa carefully gathered, selected and translated 300 Portuguese proverbs for the National Proverbs series edited by the London-based publisher Frank Palmer. In this study I intend to highlight one of the representative subject matters in Pessoa’s compilation. Furthermore, I will endeavour to trace and discuss briefly a few national and foreign proverbs that emerge in Pessoa’s literary writings. Working closely with the author’s archive and private library, I will indicate the source texts of all the proverbs referred to in each section.